1992
DOI: 10.1007/bf01623926
|View full text |Cite
|
Sign up to set email alerts
|

Targeted estrogen/progestogen replacement therapy for osteoporosis: calculation of health care cost savings

Abstract: Osteoporosis is a crippling affliction in which bone mass decreases, making it more susceptible to fracture. In postmenopausal women it presents most often as a hip, spinal, or forearm fracture. Adult women face a 15% lifetime risk of a hip fracture, and the annual costs of hip fractures alone are estimated at $7.3 billion in the United States. Since the 1970s, estrogen/progestogen therapy has been recognized as an effective intervention that reduces the risk of fractures. Recently, the development of methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Two of these studies concluded that screening followed by therapy with HRT for 15 years was cost-effective Clark and Schuttinga, 1992]. However, neither of these studies incorporated risk estimates for any of the nonskeletal effects of HRT including breast cancer, endometrial cancer, and heart disease.…”
Section: Results Of Previous Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Two of these studies concluded that screening followed by therapy with HRT for 15 years was cost-effective Clark and Schuttinga, 1992]. However, neither of these studies incorporated risk estimates for any of the nonskeletal effects of HRT including breast cancer, endometrial cancer, and heart disease.…”
Section: Results Of Previous Researchmentioning
confidence: 96%
“…Bone density screening followed by HRT was assessed in three studies OTA, 1995;Clark and Schuttinga, 1992]. Two of these studies concluded that screening followed by therapy with HRT for 15 years was cost-effective Clark and Schuttinga, 1992].…”
Section: Results Of Previous Researchmentioning
confidence: 99%
“…Bone density screening followed by HRT was assessed in 3 studies (8,10,43). Two of these studies concluded that screening followed by therapy with HRT for 15 years was cost-effective (8,43).…”
Section: Which Osteoporosis Therapies Are "Cost-effective"?mentioning
confidence: 99%
“…Two of these studies concluded that screening followed by therapy with HRT for 15 years was cost-effective (8,43). However, neither of these studies incorporated risk estimates for any of the nonskeletal effects of HRT, including breast cancer, endometrial cancer, and heart disease.…”
Section: Which Osteoporosis Therapies Are "Cost-effective"?mentioning
confidence: 99%
“…These symptoms caused by deficit of estrogen are called Pre-AND Post-menopausal syndrome and PMS (Clarke et al, 1992;Cumming et al, 1990). Conjugated equine estrogen, CEE, or chemosynthesis medical supply has been used recently to reduce or cure these symptoms.…”
Section: Introductionmentioning
confidence: 99%